PENERAPAN STRATEGI BELAJAR PETA KONSEP UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI 15 AIR JAMBAN - Rahmatika, Yelvi; Hamizi, Hamizi; Erlisnawati, Erlisnawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research is motivated by the lack of IPS students' learning outcomes, can be seen from the results of the fourth grade social studies students of SDN 15 Air Jamban with an average value of 70.55 class of 27 students 16 students who did not reach KKM with a percentage of 59.25% and the learning process which remains centered on the teacher. This research aims to improve learning outcomes IPS elementary school fourth graders 15 Air Jamban District of Mandau with learning application concept map strategies. This research is a form of classroom action research (PTK) with 2 cycles. Based on research data anlisis after applying the concept map learning strategy, the average percentage of the activity of teachers in the first cycle to 52.5% in the second cycle increased to 78.75%. The average percentage of student activity also increased, namely 51.25% in the first cycle and the second cycle increased to 76.25%. Students' scores with the basic results of the average value of 70.55 and the first cycle increased with an average value of 72.33 class with an increasing percentage of learning outcomes 2.5% and the percentage of students who completed 62.96%, and the second cycle increased into 79.22 by 12.28% percentage increase learning outcomes. The percentage of students who completed 88.88%. These results indicate that the application of learning strategies concept maps can enhance learning outcomes IPS elementary school fourth graders 15 Air Jamban.Key Words:Learning Strategy Concept Map, IPS Learning Outcomes